A Combined Theoretical and Experimental Approach to a Tyrosine Derivative with Anticancer Activity - Ganasaraswathy, D.; Vijaya, P. (Journal of Scientific Research, 2025)
4-((E)-2-(4-isopropylbenzylideneamino)ethyl)phenol (4TC) has been synthesized and characterized using spectral studies including UV-Visible and FT-IR. The anti-cancer activity of 4TC was evaluated using the MTT assay against two cancer cell lines: MDA MB 231 (human breast cancer cell line) and A549 (human lung cancer cell line). The optimized structure of 4TC is computationally constructed and theoretically studied using Gaussian 03 with the Density Functional Theory (DFT) method. This utilized the B3LYP functional with the 6-31G(d,p) basis set. Vibrational frequencies were analyzed using potential energy distribution (PED%) calculations through the vibrational energy distribution analysis (VEDA 4) program. Nonlinear optical (NLO) properties were examined based on calculated values of dipole moment (µ), polarizability (α), and first hyperpolarizability (β_tot). The polar sites of the molecules were identified using molecular electrostatic potential (MEP) surfaces, while orbital overlap was determined through the HOMO-LUMO analysis. Additionally, the electron affinity, electronegativity, chemical potential, hardness, and softness of the compounds were characterized via frontier molecular orbital (FMO) studies. In the in-silico evaluation, physicochemical parameters and drug-likeness were predicted using Swiss-ADME and pre-ADME web tools. Finally, in silico antibacterial and antifungal activity percentages were assessed using the PASS (Prediction of Activity Spectra for Substances) online tool.